Sulfur Respiration in a Marine Chemolithoautotrophic Beggiatoa Strain - Schwedt, Anne; Kreutzmann, Anne-Christin; Polerecky, Lubos; Schulz-Vogt, Heide N. (Frontiers in Microbiology, 2012)
The chemolithoautotrophic strain Beggiatoa sp. 35Flor shows an unusual migration behavior when cultivated in a gradient medium under high sulfide fluxes. As common for Beggiatoa spp., the filaments form a mat at the oxygen-sulfide interface. However, upon prolonged incubation, a subpopulation migrates actively downwards into the anoxic and sulfidic section of the medium, where the filaments become gradually depleted in their sulfur and polyhydroxyalkanoates (PHA) inclusions. This depletion is correlated with the production of hydrogen sulfide. The sulfur- and PHA-depleted filaments return to the oxygen-sulfide interface, where they switch back to depositing sulfur and PHA by aerobic sulfide oxidation. Based on these observations we conclude that internally stored elemental sulfur is respired at the expense of stored PHA under anoxic conditions. Until now, nitrate has always been assumed to be the alternative electron acceptor in chemolithoautotrophic Beggiatoa spp. under anoxic conditions. As the medium and the filaments were free of oxidized nitrogen compounds we can exclude this metabolism. Furthermore, sulfur respiration with PHA under anoxic conditions has so far only been described for heterotrophic Beggiatoa spp., but our medium did not contain accessible organic carbon. Hence the PHA inclusions must originate from atmospheric CO2 fixed by the filaments while at the oxygen-sulfide interface. We propose that the directed migration of filaments into the anoxic section of an oxygen-sulfide gradient system is used as a last resort to preserve cell integrity, which would otherwise be compromised by excessive sulfur deposition occurring in the presence of oxygen and high sulfide fluxes. The regulating mechanism of this migration is still unknown.